High‐level expression of Hsp90β is associated with poor survival in resectable non‐small‐cell lung cancer patients. Issue 4 (26th March 2015) - Kim, Seok‐Hyun; Ji, Jun Ho; Park, Kyung Tae; Lee, Ji Hyun; Kang, Kyung Woo; Park, Jae Hong; Hwang, Sang Won; Lee, Eun Hee; Cho, Yu Ji; Jeong, Yi Yeong; Kim, Ho‐Cheol; Lee, Jong Deog; et al.
Abstract : Aims: The aim of this study was to investigate the expression of Hsp90β and GRP94, and elucidate the clinical significance of their expression, in patients with resectable non‐small‐cell lung cancer (NSCLC). Methods and results: Surgical tissue specimens were obtained from 208 patients with NSCLC who underwent surgical resection. The expression levels of Hsp90β and GRP94 were assessed with tissue microarrays and immunohistochemistry. No correlations were observed between Hsp90β or GRP94 expression and several clinicopathological factors. The high‐Hsp90β group [median overall survival (OS) 20.4 months; 95% confidence interval (CI) 0.000–40.864] showed a significant decrease in OS as compared with the low‐Hsp90β group (median OS not reached; P = 0.003). In contrast to the Hsp90β analysis, the GRP94 analysis did not show a difference in OS. Moreover, in subgroup analyses of patients with squamous cell carcinoma histology, OS ( P = 0.012) and relapse‐free survival ( P = 0.044) were significantly worse in the high‐Hsp90β group than in the low‐Hsp90β group. Multivariate analysis suggested that old age [hazard ratio (HR) 1.568; 95% CI 1.019–2.412; P = 0.041], advanced disease (HR 2.066; 95% CI 1.218–3.502; P = 0.007) and high Hsp90β expression (HR 1.802; 95% CI 1.061–3.060; P = 0.029) were independent poor prognostic factors for OS. Conclusions: Hsp90β expression might be a useful marker of poor OS, although further large prospective studies are warranted to validate our findings.